Mineral and chemical composition of the Jezersko meteorite—A new chondrite from Slovenia. (October 2014) - Miler, Miloš; Ambrožič, Bojan; Mirtič, Breda; Gosar, Mateja; Šturm, Sašo; Dolenec, Matej; Jeršek, Miha
Abstract The Jezersko meteorite is a newly confirmed stony meteorite found in 1992 in the Karavanke mountains, Slovenia. The meteorite is moderately weathered (W2), indicating short terrestrial residence time. Chondrules in partially recrystallized matrix are clearly discernible but often fragmented and have mean diameter of 0.73 mm. The meteorite consists of homogeneous olivine (Fa19.4) and low‐Ca pyroxenes (Fs16.7Wo1.2), of which 34% are monoclinic, and minor plagioclase (Ab83An11Or6) and Ca‐pyroxene (Fs6Wo45.8). Troilite, kamacite, zoned taenite, tetrataenite, chromite, and metallic copper comprise about 16.5 vol% of the meteorite. Phosphates are represented by merrillite and minor chlorapatite. Undulatory extinction in some olivine grains and other shock indicators suggests weak shock metamorphism between stages S2 and S3. The bulk chemical composition generally corresponds to the mean H chondrite composition. Low siderophile element contents indicate the oxidized character of the Jezersko parent body. The temperatures recorded by two‐pyroxene, olivine‐chromite, and olivine‐orthopyroxene geothermometers are 854 °C, 737–787 °C, and 750 °C, respectively. Mg concentration profiles across orthopyroxenes and clinopyroxenes indicate relatively fast cooling at temperatures above 700 °C. A low cooling rate of 10 °C Myr−1 was obtained from metallographic data. Considering physical, chemical, and mineralogical properties, meteorite Jezersko was classified as an H4 S2(3) ordinary chondrite.